The Role Of 18F -FDG PET-CT In Assessing Bone Marrow Involvement In Diffuse Large B-Cell Lymphoma (DLBCL) - Nasir, Siti Maisarah Mohd (2018)
The role of 18F -FDG PET-CT in assessing bone marrow involvement in Diffuse Large B-Cell Lymphoma (DLBCL). In newly diagnosed DLBCL, 18F-FDG PET-CT is routinely used worldwide for staging. Bone marrow involvement is crucial in order for therapeutic purposes. Bone marrow biopsy is known as the gold standard in ruling out bone marrow involvement. This cohort study hereby assesses the role of 18F-FDG PET-CT in the detection of bone marrow involvement comparatively to bone marrow biopsy. Objective: The aim of this study is to justify the usage of 18F-FDG PETCT scan in assessing bone marrow involvement in DLBCL as appose to bone marrow biopsy.